CHOOSING AND ASSESSING EXCHANGE RATE REGIMES: A SURVEY OF THE LITERATURE - CRUZ-RODRIGUEZ,ALEXIS (ILADES. Universidad Alberto Hurtado., 2013)
This paper attempts to provide a comprehensive overview on the theoretical and empirical analysis of the selection and assessment of exchange rate regimes. The literature can be divided into two main groups: classical and modern. The first group refers to earlier studies examining the differences between floating and fixed exchange rate regimes. The second group is focused on the trade-off between credibility and flexibility, the economic performance and currency crisis, among others. In addition, this paper reviews why many countries follow de facto regimes different from their de jure regimes.